Presentation and characteristics of deep neck space abscesses: a retrospective study of 128 cases in a single institution - Al Riyami, Shaden (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Despite the development of antibiotic therapy, deep neck space abscesses continue to be potentially life-threatening conditions because of possible airway compromise and other complications. The purpose of this study was to present incidence, clinical features, management and outcomes of deep neck space abscesses, in patients admitted to a tertiary care facility over a 3-year period. Methods: Medical records of the patients diagnosed to have deep neck space abscesses in the Al Nahda Hospital from January 2009 to December 2011 were reviewed retrospectively. Data on demographic characteristics, clinical presentation, imaging modalities, treatment methods, microbiology, and outcomes were obtained. Results: A total of 30 patients (17 females and 13 males) with age ranging from 5 months to 71 years (mean age: 28.0 years) were analyzed. Majority of them presented with neck swelling, fever and pain. The parapharyngeal space (24%) was the commonest anatomical location. The majority of patients (81%) underwent incision and drainage, those remaining (19%) received intravenous antibiotics only. Culture was positive in just 17% of cases and Staphylococcus aureus was the most common organism. No patient required airway intervention. Diabetes was the most common predisposing factor. Conclusions: Early detection and treatment are essential to avoid sequelae related with deep neck space abscesses. Surgical drainage is still the cornerstone in treatment after abscesses formation. A larger, multicenter prospective study is desirable to shed further light on the correlation between risk factors, age and treatment results.